2007
DOI: 10.1016/j.catena.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil erosion and control factors by the radiometric technique in the Boussouab catchment, Eastern Rif, Morocco

Abstract: In the Eastern Rif of N Morocco, soil conservation is seriously threatened by water erosion. Large areas of soil have reached an irreversible state of degradation. In this study, the 137 Cs technique was used to quantify erosion rates and identify the main factors involved in the erosion process based on a representative catchment of the Eastern Rif. To estimate erosion rates in terms of the main factors affecting soil losses, samples were collected taking into account the lithology, slope and land use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 11 publications
2
38
1
2
Order By: Relevance
“…The 137 Cs was used by Sadiki et al (2007) to quantify erosion rates and identify main factors involved in erosion process in Boussouab catchment, Eastern Rif Morocco. It was found out that at the sampling sites, the 137 Cs activity ranged between 245 and 3670 Bq/m 2 .…”
Section: Northern Africamentioning
confidence: 99%
“…The 137 Cs was used by Sadiki et al (2007) to quantify erosion rates and identify main factors involved in erosion process in Boussouab catchment, Eastern Rif Morocco. It was found out that at the sampling sites, the 137 Cs activity ranged between 245 and 3670 Bq/m 2 .…”
Section: Northern Africamentioning
confidence: 99%
“…Sáez et al, 2011;Vericat et al, 2014), radioisotopic measurements (e.g. Sadiki et al, 2007) and bathymetric surveys (e.g. Grauso et al, 2008) have been sporadically applied in badland studies (Fig.…”
Section: Review: Methodologies For Analysing Geomorphological Processmentioning
confidence: 99%
“…Direct measurements typically involve monitoring of water flows, sediment concentrations, and turbidity to create rating curves of sediment load and water flows (Cochrane et al 2004) or by tracing radioactive isotopes observed in the eroded soils and reservoir sediments (Lu & Higgitt 2001;Nagle 2002;Sadiki et al 2007;Zheng et al 2007). Numerical models that predict or estimate soil erosion, such as the universal soil loss equation (USLE) and its revised version (RUSLE) are widely used when data from direct measurements are lacking, or to estimate the potential for soil erosion to produce sediments in a given watershed (Renard et al 1994).…”
Section: Introductionmentioning
confidence: 99%